The Brazilian “Translatinas”: Analysis of Petrobras’s Insertion in Argentina (2003-2010) - Barrera, Mariano Alejandro; Inchauspe, Eugenia (Sociedad y Economía, 2012)
This article aims to analyze, first, the internationalization of brazilian firms in South America and, in turn, what are the main features of the investment in the region and particularly in Argentina. Second, seeks to address how was the inclusion of the Petrobras Argentina hydrocarbon market. The purpose of this case study is to determine whether the internalization of Petrobras is expressed as a virtuous process within the regional integration agreement or, conversely, assumes the characteristics of any other multinational company. Hence, it is intended to highlight the limitations presented by the regional development process are presented as points of intersection between the trends of deepening Mercosur and . status quo